2022
DOI: 10.6007/ijarbss/v12-i1/11854
|View full text |Cite
|
Sign up to set email alerts
|

Role of Health and Safety Management Practices in Safety Performance of Malaysian Bumiputera SMEs

Abstract: Small and medium enterprises (SMEs) are widely acknowledged as the backbone of the Malaysian economy. Therefore, it is very important that SMEs manage occupational health and safety adequately. The purpose of this paper is to investigate safety management practices and its associations with the safety performance in Malaysian Bumiputera SMEs. A safety management system reflects the organization's commitment to safety which will result in improved safety performance; thus, it is worth investigating. In particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Key challenges to employee health and wellbeing in SMEs include stress and its impact on mental and physical health, uncertainty due to organizational and social change, and work-life balance (Van Dick, 2023). Safety management practices play a role in improving the safety performance of Malaysian Bumiputera SMEs (Abdullah et al, 2022). Therefore, it can be concluded that prioritizing health and wellbeing in the workplace can contribute to the overall performance of SMEs.…”
Section: ) Employee Health and Welfarementioning
confidence: 99%
“…Key challenges to employee health and wellbeing in SMEs include stress and its impact on mental and physical health, uncertainty due to organizational and social change, and work-life balance (Van Dick, 2023). Safety management practices play a role in improving the safety performance of Malaysian Bumiputera SMEs (Abdullah et al, 2022). Therefore, it can be concluded that prioritizing health and wellbeing in the workplace can contribute to the overall performance of SMEs.…”
Section: ) Employee Health and Welfarementioning
confidence: 99%